1990
DOI: 10.1111/j.1365-3016.1990.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia during pregnancy as a risk factor for infant iron deficiency: report from the Valencia Infant Anaemia Cohort (VIAC) study

Abstract: A prospective cohort study with a 1-year follow-up of 156 neonates was carried out specifically designed to test the hypothesis that there is a positive relationship between iron deficiency during pregnancy and the development of the same disease in newborn infants. Exposure was defined as being born of a mother with ferropenic anaemia at delivery, and cases as the infants who developed iron deficiency during their first year of life. A statistically significant positive association was detected with an odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 12 publications
5
93
1
8
Order By: Relevance
“…Employing standardized methods, the large study examined clusters of three countries and involved 11 750 mothers and their infants. Three other studies, from Spain, Jordan and Indonesia (25)(26)(27) , demonstrated a higher incidence of ID or IDA in infants born to mothers with IDA during pregnancy, as compared with infants born to mothers with adequate Fe status.…”
Section: Discussionmentioning
confidence: 86%
“…Employing standardized methods, the large study examined clusters of three countries and involved 11 750 mothers and their infants. Three other studies, from Spain, Jordan and Indonesia (25)(26)(27) , demonstrated a higher incidence of ID or IDA in infants born to mothers with IDA during pregnancy, as compared with infants born to mothers with adequate Fe status.…”
Section: Discussionmentioning
confidence: 86%
“…Los niveles de ferritina de lactantes menores hijos de madres que recibieron suplementación con hierro durante el embarazo son significativamente más elevados que los de hijos de madres no suplementadas con hierro 33 . Por otra parte los hijos de madres con anemia ferropriva al momento del parto tienen una mayor prevalencia de anemia ferropriva durante el primer año de vida habiéndose controlado otros factores confundentes [38][39][40] .…”
Section: Consecuencias De La Deficiencia De Hierro En El Embarazounclassified
“…It was long believed that only severe IDA during pregnancy affects fetal Fe stores; in fact, some studies (Siimes & Siimes, 1986;Harthoorn-Lasthuizen et al 2001) have shown no differences in neonatal Fe status indices between infants born to Fe-deficient and Fe-replete mothers. However, recent studies with longer-term follow-up (Colomer et al 1990;Kilbride et al 1999;de Pee et al 2002) have shown that infants born to Fe-deficient anaemic mothers have a higher incidence of Fe deficiency and anaemia later in infancy than infants born to Fe-replete mothers.…”
Section: Fetal Iron Accretion and Erythropoiesismentioning
confidence: 99%